Touch-actuated microneedle array patch for closed-loop transdermal drug delivery - Jingbo Yang; Zhipeng Chen; Rui Ye; Jiyu Li; Yinyan Lin; Jie Gao; Lei Ren; Bin Liu; Lelun Jiang (Taylor & Francis Group, 2018)
To date, only approximately 20 drugs synthesized with small molecules have been approved by the FDA for use in traditional transdermal patches (TTP) owing to the extremely low permeation rate of the skin barrier for macromolecular drugs. A novel touch-actuated microneedle array patch (TMAP) was developed for transdermal delivery of liquid macromolecular drugs. TMAP is a combination of a typical TTP and a solid microneedle array (MA). High doses of liquid drug formulations, especially heat-sensitive compounds can be easily filled and stored in the drug reservoir of TMAPs. TMAP can easily penetrate the skin and automatically retract from it to create microchannels through the stratum corneum (SC) layer using touch-actuated 'press and release' actions for passive permeation of liquid drugs. Comparison of subcutaneous injection, TTP, solid MA, and dissolvable MA, indicated that insulin-loaded TMAP exhibited the best hypoglycemic effect on type 1 diabetic rats. A 'closed-loop' permeation control was also provided for on-demand insulin delivery based on feedback of blood glucose levels (BGLs). Twenty IU-insulin-loaded TMAP maintained the type 1 diabetic rats in a normoglycemic state for approximately 11.63 h, the longest therapeutic duration among all previously reported results on microneedle-based transdermal patches. TMAP possesses excellent transdermal drug delivery capabilities.